Tapetal 3-Ketoacyl-Coenzyme A Synthases Are Involved in Pollen Coat Lipid Accumulation for Pollen-Stigma Interaction in Arabidopsis - Zhang, Zaibao; Zhan, Huadong; Lu, Jieyang; Xiong, Shuangxi; Yang, Naiying; Yuan, Hongyu; Yang, Zhong-Nan (Frontiers in Plant Science, 2021)
Pollen coat lipids form an outer barrier to protect pollen itself and play essential roles in pollen-stigma interaction. However, the precise molecular mechanisms underlying the production, deposition, regulation, and function of pollen coat lipids during anther development remain largely elusive. In lipid metabolism, 3-ketoacyl-coenzyme A synthases (KCS) are involved in fatty acid elongation or very-long-chain fatty acid (VLCFA) synthesis. In this study, we identified six members of the Arabidopsis KCS family expressed in anther. Among them, KCS7, KCS15, and KCS21 were expressed in tapetal cells at anther stages 8–10. Further analysis demonstrated that they act downstream of male sterility 1 (MS1), a regulator of late tapetum development. The kcs7/15/21 triple mutant is fertile. Both cellular observation and lipid staining showed pollen coat lipid was decreased in kcs7/15/21 triple mutant. After landing on stigma, the wild-type pollen grains were hydrated for about 5 min while the kcs7/15/21 triple mutant pollen took about 10 min to hydrate. Pollen tube growth of the triple mutant was also delayed. These results demonstrate that the tapetum-localized KCS proteins are involved in the accumulation of pollen coat lipid and reveal the roles of tapetal-derived pollen coat lipid for pollen-stigma interaction.